Crop protection for small-scale farmers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
'Crop Protecton for Small-Scale Farms in East and Central Africa - a Review' edited by Roslyn Tamara Prinsiey of the CSC and P John Terry, Weed Research Department of Agricultural Sciences, University of Bristol UK, ISBN 0 85092 331 X, price UKL6.00